Safety of nursing professionals and patient facing COVID-19 pandemic in critical care unit - Juliana Rizzo Gnatta; Rita de Cássia Almeida Vieira; Luciana Soares Costa Santos; Sirlene Luz Penha; Giovanna Nogueira Sanchez; Jussiely Cunha Oliveira; Eduesley Santana-Santos; Maria de Fatima Fernandes Vattimo (Universidade de São Paulo, 2023)
Abstract Objective: to evaluate nursing professionals and patient safety culture during the professional performance in the care of suspected or infected patients with COVID-19. Method: a cross-sectional study carried out with 90 professionals from critical care units of two teaching hospitals. An instrument for sociodemographic characterization and health conditions was used, in addition to the constructs "Nursing professional and patient safety" and the Hospital Survey on Patient Safety Culture. Univariate analyzes were performed between the diagnosis of COVID-19 and the characteristics of Nursing professionals, applying Kendell's correlation between the constructs. Results: the COVID-19 diagnosis presented a significant statistical difference between nursing professionals that worked for more than six years at the critical care unit (p=0.020) and the items of the construct "Nursing professional and patient safety" regarding the doubts about how to remove the personal protective equipment (p=0.013) and safety flow (p=0,021). The dimensions 2 (p=0.003), 3 (p=0.009), 4 (p=0.013), 6 (p<0.001), and 9 (p=0.024) of the Hospital Survey on Patient Safety Culture were associated with the accomplishment of training. Conclusion: a higher professional nursing experience time was associated with non-infection by COVID-19. The perception of the safety culture of the patient was related to the accomplishment of training.